Global partnership in response to COVID-19 - Arbeiter, Jana (Annales. Series historia et sociologia, 2022)
The paper analyses the response of the international development system aimed at offsetting the effects of the COVID-19 pandemic in less developed countries through the prism of Sustainable Development Goals (SDGs). We apply a mixed-method approach, comparing the response of the international development system to the international cooperation targets under Goal 17 of the SDGs. The results of a comparative-historic analysis, the conceptualization and operationalization of key concepts, the case-study analysis, a secondary statistical analysis, and a secondary sources analysis indicate that the tools envisaged by SDG 17 for its implementation (increase of several financial resources for development, debt relief, COVAX, etc.) have not been adequately used by the international community to counter the impact of COVID-19 on development.
Keywords: COVAX; Covid-19; globalno partnerstvo; Mednarodna skupnost; Mednarodno sodelovanje; razvojno sodelovanje; Trajnostni razvoj